The impact of international financial reporting standard (IFRS) on value relevance of accounting information: Evidence from Nigeria - Sullubawa, Nabila Kabir (2015)
Value relevance as a field of study has been growing rapidly and gaining attention by many scholars. Value relevance was also viewed as extent of association between accounting information and market value. Therefore, the main objective of this study is to investigate the value relevance of accounting information among listed companies in Nigeria. The study also examined the impact of IFRS on value relevance of accounting information of Nigerian listed companies where, 68 listed companies in NSE were used as the sample of the study over the period of 6 years (2009-2014). It investigated the pre-IFRS period from 2009-2011 and post-IFRS period from 2012-2014. The study used pooled OLS model to analyze the data extracted from Thompson Reuters online data stream. Furthermore, the study found that accounting information of listed companies in Nigeria as value relevant using the Ohlson model where, both book value of equity and earnings are positively and significantly related to market value of equity. More also, the study found that value relevance of both earnings and book value of equity has increased in the post-IFRS period